Segregated finite element solution of the incompressible Navier-Stokes equations, with equal-order velocity-pressure formulation - Zijl, G. P. A. G. van (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1990.